Contributions of human performance evaluations to the achievement of objectives in the public sector (Research, Society and Development, 2020)
The Brazilian public administration has undergone great changes, and in this context human performance evaluations have emerged as a means of promoting improved government performance. Based on this assumption, this work aimed to identify in the national literature the contributions of performance evaluations to the achievement of strategic objectives in the public sector between 2009 and 2019. For this purpose, a bibliographic survey was conducted on the platform of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), based on publications from 2009 onwards. As a result, 8 articles were obtained on performance management and evaluation, motivation and server development. It was concluded that the implementation of the private model in public administration without in-depth debate does not provide improvements in public service. Therefore, human resource managers should adapt it to the reality of the public sector to make it more effective.